Tramas do impedimento: os sentidos da desistência entre Alfabetizandos da EJA - Cardoso, Cícera Romana (2007)
For young people and adults that have not yet conquered reading and writing, being literate is the most important thing in life , a dream . Scholarly learning for them is like hegemonic knowledge in contemporary literate society. Thus, for them to get into school is to be able to have such knowledge and, through it, feel inserted into this society. However, along this process of learning, they start to drop out, little by little, statistically increasing the number of people who give up on young people and adult education Eja, as well as slowly reducing the contingent of illiteracy in the country. With this reality as a starting point, we question the concrete and symbolic reasons or motives that lead to a dropping out of the literacy classes at Eja. To do so, we have established, as the object of our study, the feelings of giving up among those involved in young people and adult literacy training. To understand such feelings is our purpose in this investigation. The theory of Social Representations (MOSCOVICI, 1978, 2004) was the theoretical-methodological option for subsidizing data search, analyses and interpretation, making us perceive the significance of the object of this study for these individuals. The gathering of such symbolic content involved the use of semi-structured interviews with eleven drop-outs and ten students who had repeated this modality of teaching in public schools in Natal, RN, during the 2006 school year. From the thematic and categorical analyses (BARDIN, 1977), we identified elements that gave support to some themes. Later, these themes led to three categories, suggesting that feelings associated with dropping out were based on the following: learning difficulties because they did not understand the contents; having their lack of knowledge exposed, thus bringing forth feelings of shame, humiliation, and embarrassment for not knowing how to read and write at a mature age; work, tiredness and sickness. The students who manage to remain in school are those who force themselves to live with the feelings of maladaptation and those who develop a sense of adaptation the other way round to the institution, that is, acceptance of institutional failures and omissions